Prevalence of condylar morphological changes in individuals with class II malocclusion - Oliveira, Daniela Fernandes Lobo Molica [UNESP]; Fernandes, Ellen Eduarda [UNESP]; Lopes, Sergio Lúcio Pereira de Castro [UNESP]; Rode, Sigmar de Mello [UNESP]; Oliveira, Wagner de [UNESP]; Ertty, Ertty; Cardoso, Mauricio de Almeida; Tien-Li, An; Meloti, Fernanda (FapUNIFESP (SciELO), 2024)
This observational, cross-sectional study with retrospective collection was aimed to evaluate the prevalence of morphological changes in mandibular condyles in individuals with class II malocclusion, classified according to different vertical growth patterns (brachyfacial, mesofacial, and dolichofacial), through cone beam computed tomography (CBCT). Seventy CBCT images (140 mandibular condyles) were selected from individuals without orthodontic treatment, of both sexes, aged between 25 and 50 years. No statistically significant differences were found between facial patterns; however, there was a higher relative prevalence of bone changes in dolichofacial individuals with flattening (62%), sclerosis (44%), and subchondral bone cyst (20%). Erosion and osteophytes prevailed in mesofacial (39%), and brachyfacial individuals (32%), respectively. Thus, there was no statistically significant difference in the prevalence of degenerative changes between the vertical skeletal patterns. Flattening was the most prevalent change, whereas subchondral bone cyst was the least prevalent among the three groups studied. The observational design of this study makes it possible to analyze image banks to verify the correlation of morphological changes in the temporomandibular joint in different facial patterns in patients with class II malocclusion. A limitation of the study is that clinical characteristics were not evaluated.
Keywords: Cone-Beam Computed Tomography; Mandibular Condyle; Osteoarthritis